2000
DOI: 10.1590/s0101-81752000000100001
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura populacional de Armases angustipes (Dana) (Decapoda, Brachyura, Grapsidae) na Ilha do Farol, Matinhos, Paraná

Abstract: ABSTRACT. Population structure of Armases anguslipes (Dana) (Decapoda, Brachyura, Grapsidae) from Farol Island, Matinhos, Paraná. Annual fluctuation of densities and population structure ofArmases angustipes (Dana, 1852) from a rocky shore at Farol Island, Matinhos, Paraná, Brazil (25°51 'S and 48°32'W) were studied. The population structure was treated in the following aspects: sexual proportion, dial intensity of activities, size composition and its fluctuation, and general condition of the crabs. The collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
2
5
3
Order By: Relevance
“…A comparison of the previous description of the larval development of A. angustipes (Kowalczuk, 1994) and the present results is given in Table 2. The setation of the carapace was not described by Kowalczuk (1994) and therefore this character cannot be compared here; a detailed description is given above (see text and figures).…”
Section: Maxillasupporting
confidence: 57%
See 3 more Smart Citations
“…A comparison of the previous description of the larval development of A. angustipes (Kowalczuk, 1994) and the present results is given in Table 2. The setation of the carapace was not described by Kowalczuk (1994) and therefore this character cannot be compared here; a detailed description is given above (see text and figures).…”
Section: Maxillasupporting
confidence: 57%
“…Another important difference was observed on the inner surface of the scaphognathite of the megalopal maxilla. In the present study, two setae were observed on the anterior and one seta on the posterior area; the latter was not described by Kowalczuk (1994). This is significant insofar as the setation (2 + 1) is a typical character which allows one to distinguish sesarmid megalopae from all other grapsoid megalopae (Cuesta, 1999).…”
Section: Maxillacontrasting
confidence: 46%
See 2 more Smart Citations
“…angustipes (Dana, 1852) by Kowalczuk (1994) and Cuesta and Anger (2001);A. miersii (Rathbun, 1897) by Zimmermann-Ruf (1997) and Cuesta et al (1999), and most recently A. benedicti (Rathbun, 1897) by Lima and Abrunhosa (2006).…”
Section: Introductionmentioning
confidence: 99%